Kinematically heterogeneous faulting in the configuration of Neogene Patagonian foreland basins: activation of pre-existing fabrics and strain partitioning - García, Micaela Romina (2019)
The retroarc of the North Patagonian Andes was configured by the uplift of basement blocks limited by faults strongly oblique to the Andean chain. These fault systems defined the Patagonian Broken Foreland, characterized by a series of Neogene basins distributed along the reatroarc system. Several interpretations about the origin of this tectonic scenario have been devised in recent years. On the one hand, a partitioning of deformation is proposed as the main control in the configuration of the main cordillera and the foreland zone as a result of oblique convergence between Nazca y South America plates. Contrarily, reactivation of Paleozoic and Mesozoic crustal anisotropies was suggested to explain the configuration of thick-skinned-dominated tectonics during the last contractional Andean orogeny phase. Nevertheless, detailed studies that tested the relationship between the Paleozoic and Mesozoic crustal weaknesses with Andean structures have not yet been developed. This uncertainty determines an ambiguous tectonic framework in which kinematic analysis is absent.The Sañicó Massif presents uplifted basement blocks with well-exposed fault zones associated with a thin record of intermontane basin infill. The work was carried out based on morphostructural and microstructural studies of pre-existing basement fabrics and the Andean structures. The basement fabrics (regional metamorphic foliation and ductile shear zones) present a close location and geometric relationship with all extensional Mesozoic and Andean faults. Kinematic results of small-scale faults show heterogeneous patterns due to the interaction of pre-existing fabrics reactivation, multiple deformations and subgroups of new faults.The results indicate a three-dimensional deformation model in the foreland zone, fundamentally controlled by the activation of Paleozoic basement fabrics and tectonic inversion of Mesozoic extensional faults. In turn, the small-scale structures present a heterogeneous distribution, which could be linked to the response of convergence direction. Although the results demonstrate a strong control of pre-existing weaknesses, mechanical models of deformation that reproduce the observed kinematic model, can provide insight into the natural conditions of deformation. Hence, analogue models will represent a functional tool for testing the influence of structural inheritance as well as, the progressive deformation undergone during different tectonic conditions.